1997
DOI: 10.2307/1131844
|View full text |Cite
|
Sign up to set email alerts
|

Vagal Regulation of Heart Rate in the Prediction of Developmental Outcome for Very Low Birth Weight Preterm Infants

Abstract: To investigate heart rate and respiratory sinus arrhythmia (RSA) as markers of developmental outcome, infant ECG and 3 year outcome were assessed in 41 very low birth weight (< 1,500 g) infants. Measures of mean heart rate and RSA, and the maturational shifts in their values from 33 to 35 weeks gestational age, were recorded. RSA measures predicted 3 year outcome beyond the effects of birth weight, medical risk, and socioeconomic status. Higher RSA was associated with better social skills, whereas greater RSA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
92
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 135 publications
(100 citation statements)
references
References 0 publications
7
92
1
Order By: Relevance
“…The failure to suppress RSA in response to environmental challenge is consistent with previous findings that infants with regulatory disorders did not regulate (decrease) RSA from baseline to a task (DeGangi et al, 1991). Since other studies have indicated that there is a positive association between vagal regulation and both concurrent and future behavioral regulation during frustration (Calkins, 1997) and social tasks (Doussard-Roosevelt, Porges, Scanlon, Alemi, & Scanlon, 1997;Stifter & Corey, 2001;Suess & Bornstein, 2000), the findings of the current study suggest that infants who were exposed to cocaine may be at risk for less adaptive behavioral regulation during environmental challenges.…”
Section: Discussionsupporting
confidence: 90%
“…The failure to suppress RSA in response to environmental challenge is consistent with previous findings that infants with regulatory disorders did not regulate (decrease) RSA from baseline to a task (DeGangi et al, 1991). Since other studies have indicated that there is a positive association between vagal regulation and both concurrent and future behavioral regulation during frustration (Calkins, 1997) and social tasks (Doussard-Roosevelt, Porges, Scanlon, Alemi, & Scanlon, 1997;Stifter & Corey, 2001;Suess & Bornstein, 2000), the findings of the current study suggest that infants who were exposed to cocaine may be at risk for less adaptive behavioral regulation during environmental challenges.…”
Section: Discussionsupporting
confidence: 90%
“…For example, the HRV parameters among our premature infants were all somewhat lower than those reported by those evaluating HRV in term infants (50,51), consistent with reports that HRV parameters are lower among infants of lower postconceptional age (21,22,25,36,50,(52)(53)(54). Likewise, our results for the values of HRV parameters in pediatric oncology patients are similar to those found in earlier studies (13); values for HRV parameters in oncology patients may be lower than healthy children of similar ages due to cardiac toxicity of anthracycline chemotherapy, pain or other symptoms (55).…”
Section: Hrv Outlier Methodssupporting
confidence: 90%
“…The vagus is a cranial nerve that runs from the brain stem at the nucleus ambiguous to various body organs, which include the heart and digestive system, and promote dynamic feedback between the brain centers and the organs that regulate homeostasis. This coordinating role has led researchers to describe RSA not only as an index of neural control of the heart but also as an assessment of underlying regulatory abilities in mammals (Doussard-Roosevelt, Porges, Scanlon, Alemi, & Scanlon, 1997).…”
Section: Self-regulation At the Physiological Levelmentioning
confidence: 99%